A Criminological Study of the Impact of Domestic Violence on Child Abuse - Udayakumara Amarasinghe, (Indian Journal of Social Science and Literature (IJSSL), 2025)
There is a close relationship between domestic violence and child abuse. Although many children are victims of domestic violence, very few of them are reported to legal institutions. The main reason for this is that the abuser is a family member. However, the harm caused to children by domestic violence cannot be underestimated. This study was conducted on children in Sri Lanka who are victims of domestic violence, and specifically studied the factors that affect the victimisation of domestic violence and the effects it has on children. The economic and social status of the families of children who are victims of domestic violence was also discussed. A sample of 40 children who were victims of domestic violence was used for the study. Accordingly, the main objective of conducting this research is to study the factors that affect the victimisation of children in the family and the abuse situations that children face. Accordingly, the % of direct problems with the child alone is 47%. 53% of children have experienced violence due to disputes between their parents. It was also revealed that 90% of the siblings of the children who have been victims of violence have also been subjected to violence. Parents in the 26-33 and 34-40 age groups are primarily involved in domestic violence. Accordingly, this study revealed that in families with young and underage parents in this country, family disputes are more common, and children are primarily affected. The father's drug use, the family's economic problems, the low education of the parents, poor interpersonal relationships between the parents, living in a single-parent family, and various weaknesses of the children are the main factors that affect domestic violence against children.